Respostas
respondido por:
6
M - 1/2 . (m + 3/2) = 2/5 . (1 - m/2)
1(m + 3/2) 2(1 - m/2)
m - ------------------- = ----------------
2 5
(m + 3/2) (2 - 2m/2)
m - ----------------- = -----------------SOMA com fração faz mmc 2x5 = 10
2 5
10(m) - 5(m + 3/2) = 2(2 - 2m/2)
------------------------------------------------- fração com (=) igualdade
10 despreza o denominador
10(m) - 5(m + 3/2) = 2(2 - 2m/2)
10m - 5m + 5(3/2) = 4 - 2(2m/2)
5m + 5(3)/2 = 4 - 2(2m)/2
5m + 15/2 = 4 - 4m/2
5m + 15/2 = 4 - 2m
5m + 15/2 + 2m = 4
5m + 2m = 4 - 15/2
7m = 4 - 7,5
7m = - 3,5
m = - 3,5/7
m = - 0,5
m = - 5/10 ( divide AMBOS por 5)
m = - 1/2
1(m + 3/2) 2(1 - m/2)
m - ------------------- = ----------------
2 5
(m + 3/2) (2 - 2m/2)
m - ----------------- = -----------------SOMA com fração faz mmc 2x5 = 10
2 5
10(m) - 5(m + 3/2) = 2(2 - 2m/2)
------------------------------------------------- fração com (=) igualdade
10 despreza o denominador
10(m) - 5(m + 3/2) = 2(2 - 2m/2)
10m - 5m + 5(3/2) = 4 - 2(2m/2)
5m + 5(3)/2 = 4 - 2(2m)/2
5m + 15/2 = 4 - 4m/2
5m + 15/2 = 4 - 2m
5m + 15/2 + 2m = 4
5m + 2m = 4 - 15/2
7m = 4 - 7,5
7m = - 3,5
m = - 3,5/7
m = - 0,5
m = - 5/10 ( divide AMBOS por 5)
m = - 1/2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás